Evaluation of soluble fibrin monomer complex in patients in SARS‐CoV‐2 COVID‐19 infection‐associated coagulopathy. (10th January 2022) - Sridharan, Meera; D. Navitskas, Serena; M. Kock, Elizabeth; E. Houghton, Damon; M. Heikal, Nahla; Chen, Dong; K. Pruthi, Rajiv
Abstract: Hospitalized patients with COVID‐19 infection frequently have coagulopathy resembling disseminated intravascular coagulation (DIC). An elevation of D‐dimer level is associated with a poor prognosis; however, the role of other fibrin degradation products, such as soluble fibrin monomers (SFMC), is not known. The objective of the study was to investigate the frequency and prognostic role of elevated SFMC in patients with COVID‐19. In this retrospective cohort study, patients hospitalized between April 1,  2020 and December 14, 2020 at Mayo Clinic with COVID‐19 infection who underwent DIC panel testing were identified. Results of laboratory tests and outcomes (thrombosis and death) within 40 days of testing were obtained via medical record review. Of 108 patients, D‐dimer was elevated in 82 (75.9%) patients. Of those with elevated D‐dimer, SFMC was elevated in 19/82 (23%) patients. There were 16 thrombotic events and 16 deaths during the 40‐day follow‐up. The incidence of overt‐DIC was 4.6%. In univariate analysis, D‐dimer ≥5 x highest upper limit normal (ULN) and elevated SFMC were each associated with higher 40‐day mortality. However, when used in combination with D‐dimer ≥5 x highest ULN, an elevated SFMC provided no further mortality predictive value. Compared to 75.9% of patients with elevated D‐dimers, of those tested, only 23% had elevated SFMC. These results support the hypothesis that elevated D‐dimer in COVID‐19 infection is a direct consequence of endothelial damage and not overt‐DIC.